Isaiah Berlin : a value pluralist and humanist view of human nature and the meaning of life - Aarsbergen-Ligtvoet, Connie, 1961- (Currents of encounter, 2006)
"This study describes the anthropology of Sir Isaiah Berlin (1909-1997), value pluralism's founding father. Berlin wants to protect both moral and cultural diversity against monist tendencies but at the same time struggles to avoid moral relativism. This study follows Berlin critically in this dilemma, thereby giving insight into how value pluralism differs from contemporary postmodernist and conventionalist positions."--Jacket